Gastrointestinal endoscopy during the coronavirus pandemic in the New York area: results from a multi-institutional survey - Mahadev, Srihari; Aroniadis, Olga C.; Barraza, Luis H.; Agarunov, Emil; Smith, Michael S.; Goodman, Adam J.; Benias, Petros C.; Buscaglia, Jonathan M.; Gross, Seth A.; Kasmin, Franklin; Cohen, Jonathan; Carr-Locke, David L.; Greenwald, David; Mendelsohn, Robin; Sethi, Amrita; Gonda, Tamas A.; (on behalf of NYSGE research committee) (Endoscopy International Open, 2020)
Background and study aims The coronavirus disease 2019 (COVID-19), and measures taken to mitigate its impact, have profoundly affected the clinical care of gastroenterology patients and the work of endoscopy units. We aimed to describe the clinical care delivered by gastroenterologists and the type of procedures performed during the early to peak period of the pandemic. Methods Endoscopy leaders in the New York region were invited to participate in an electronic survey describing operations and clinical service. Surveys were distributed on April 7, 2020 and responses were collected over the following week. A follow-up survey was distributed on April 20, 2020. Participants were asked to report procedure volumes and patient characteristics, as well protocols for staffing and testing for COVID-19. Results Eleven large academic endoscopy units in the New York City region responded to the survey, representing every major hospital system. COVID patients occupied an average of 54.5 % (18 – 84 %) of hospital beds at the time of survey completion, with 14.5 % (2 %-23 %) of COVID patients requiring intensive care. Endoscopy procedure volume and the number of physicians performing procedures declined by 90 % (66 %-98 %) and 84.5 % (50 %-97 %) respectively following introduction of restricted practice. During this period the most common procedures were EGDs (7.9/unit/week; 88 % for bleeding; the remainder for foreign body and feeding tube placement); ERCPs (5/unit/week; for cholangitis in 67 % and obstructive jaundice in 20 %); Colonoscopies (4/unit/week for bleeding in 77 % or colitis in 23 %) and least common were EUS (3/unit/week for tumor biopsies). Of the sites, 44 % performed pre-procedure COVID testing and the proportion of COVID-positive patients undergoing procedures was 4.6 % in the first 2 weeks and up to 19.6 % in the subsequent 2 weeks. The majority of COVID-positive patients undergoing procedures underwent EGD (30.6 % COVID +) and ERCP (10.2 % COVID +).Conclusions COVID-19 has profoundly impacted the operation of endoscopy units in the New York region. Our data show the impact of a restricted emergency practice on endoscopy volumes and the proportion of expected COVID positive cases during the peak time of the pandemic.